The Politics and Government of Switzerland - Church, C. author. aut Link
XIV, 285 p.
Keywords: The Politics and Government of Switzerland is one of very few English language studies of contemporary Swiss politics. Drawing on recent research in Switzerland, and the author's own observations, it offers wide coverage of Swiss political forces, processes and policies. Church argues that Switzerland is actually a vibrant and pluralist polity, in which politics are increasingly competitive. However, it still retains some distinctive characteristics like direct democracy, which mean that the Swiss people play a larger role than in other countries.